2011
DOI: 10.1108/08876041111143104
|View full text |Cite
|
Sign up to set email alerts
|

Do relationship benefits and maintenance drive commitment and loyalty?

Abstract: PurposeThis paper seeks to examine the central role that commitment plays in driving customer loyalty and to identify the effect that confidence, social and special treatment benefits as well as relationship investment, communication and management have on the development of commitment, and ultimately customer loyalty.Design/methodology/approachThe paper reports the results of a national mail survey of 591 consumers across nine different service industries.FindingsThe findings of the study suggest that relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(153 citation statements)
references
References 49 publications
13
138
0
2
Order By: Relevance
“…The finding of this study was also consistent with previous studies (Dagger et al, 2011;Tanford et al, 2010;Adidam et al, 2004;Park and Him, 2003) that relationship benefits characterized as superior quality of services relative to other suppliers have a positive influence on relationship commitment. The construct of relationship benefits is a significant determinant of relationship commitment; PTE providers may consider enhance their benefits provided to students in order to increase students' commitment to schools.…”
Section: Discussionsupporting
confidence: 82%
“…The finding of this study was also consistent with previous studies (Dagger et al, 2011;Tanford et al, 2010;Adidam et al, 2004;Park and Him, 2003) that relationship benefits characterized as superior quality of services relative to other suppliers have a positive influence on relationship commitment. The construct of relationship benefits is a significant determinant of relationship commitment; PTE providers may consider enhance their benefits provided to students in order to increase students' commitment to schools.…”
Section: Discussionsupporting
confidence: 82%
“…Trust plays an important role in behavioral variables, mainly in customers' propensity to keep and expand relationships with the same service provider, empowering retention (Morgan & Hunt, 1994;Singh & Sirdeshmukh, 2000). It has been highlighted that trust is crucial for service providers that adopt customer retention strategies (Dagger, David, & Ng, 2011).…”
Section: Proposed Theoretical Model and Research Hypothesesmentioning
confidence: 99%
“…Recently, Fraering and Minor (2013) discovered satisfaction and loyalty can lead to fortitude that sustains repurchase behavior and a sense of community that ultimately benefits firms. Dagger et al (2011) found support for the idea confidence, social and special treatment benefits affect commitment to the service, which is positively related to loyalty. Their conclusion was that these benefits add value to the customer's service experience beyond the core products, allowing firms to benefit from higher value loyal customers.…”
Section: Introductionmentioning
confidence: 87%
“…For companies, lowering customer defection rates can lead to increasing profits and possibly lower costs as it can be less expensive to keep existing customers than to acquire new customers (Reichheld and Sasser, 1990;Pine et al, 2009). From the customer's perspective, relationships with service providers can reduce the perceived risk of evaluating services which are primarily intangible (Berry, 1995) and provide customers with valued benefits (e.g., Czepiel, 1990;Dagger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%